Clinical Effects of the Probing Method with Depth Gauge for Determining the Screw Depth of Locking Proximal Humeral Plate. (15th November 2016) - Jin, Lin; Guo, Jialiang; Guo, Junfei; Yin, Yingchao; Hou, Zhiyong; Zhang, Yingze
Abstract : Background . The use of locking plates has gained popularity to treat proximal humeral fractures. However, the complication rates remain high. Biomechanical study suggested that subchondral screw-tip abutment significantly increased the stability of plant. We present a simple method to obtain the proper screw length through the depth gauge in elderly patients and compared the clinical effects with traditional measuring method. Methods . 40 patients were separated into two groups according to the two surgical methods: the probing method with depth gauge and the traditional measuring method. The intraoperative indexes and postoperative complications were recorded. The Constant and Murley score was used for the functional assessment in the 12th month. Results . Operative time and intraoperative blood loss indicated no statistical differences. X-ray exposure time and the patients with screw path penetrating the articular cartilage significantly differed. Postoperative complications and Constant and Murley score showed no statistical differences. Conclusions . Probing method with depth gauge is an appropriate alternative to determine the screw length, which can make the screw-tip adjoin the subchondral bone and keep the articular surface of humeral head intact and at the same time effectively avoid frequent X-ray fluoroscopy and adjusting the screws.